Co-regulation of two tandem genes by one blue-light element in Neurospora crassa - S. PIETSCHMANN; J. EBERLE; F.-R. LAUTER; N. N. PANDIT; V. E. A. RUSSO (Fungal Genetics Reports, 1991)
Many genes of Neurospora crassa are regulated by blue light: al-1 (Schmidhauser et al. 1990 Mol. Cell. Biol. 10:5064-5070), al-2 (Lauter, Schmidhauser, Yanofsky, Russo unpublished), al-3 (Nelson et al. 1989 Mol. Cell. Biol. 9:1271-1276), bli-3, bli-4, bli-7, bli-13 (Sommer et al. 1989 NAR 17:5713-5723). For none of these genes are the blue light cis-regulatory sequences (blue-light elements, BE) known. Here we report the presence of such BE in front of bli-4.